Monetização dos riscos no meio ambiente do trabalho uma leitura a partir do liberalismo igualitário - TAVARES, Sílvia Gabriele Corrêa (Universidade Federal do Pará, 2015)
This thesis analyses the Risks Monetization in the Work Environment – phenomenon that authorizes the financial compensation for the worker due to his exposure to risks existing in the place of work –, which is done by the optics of the Egalitarian Liberalism of John Rawls and Ronald Dworkin. The first chapter analyses and compares the liberal egalitarian theories presented by John Rawls and Ronald Dworkin with the Economic Analysis of the Law theory of Richard Posner. The second chapter demonstrates which are the brazilian juridical practices related to the risks monetization. The third chapter makes a norm and principles based analysis in order to answer if it is necessary to reform those practices, analyzing, yet, which are the obstacles for the effective workers protection.